Macrophage migration inhibitory factor: a potential biomarker for chronic low back pain in patients with Modic changes. Issue 2 (3rd August 2021) - Gjefsen, Elisabeth; Gervin, Kristina; Goll, Guro; Bråten, Lars Christian Haugli; Wigemyr, Monica; Aass, Hans Christian D; Vigeland, Maria Dehli; Schistad, Elina; Pedersen, Linda Margareth; Pripp, Are Hugo; Storheim, Kjersti; Selmer, Kaja Kristine; et al.
Abstract : Background: Low back pain (LBP) is a leading cause of disability worldwide, but the aetiology remains poorly understood. Finding relevant biomarkers may lead to better understanding of disease mechanisms. Patients with vertebral endplate bone marrow lesions visualised on MRI as Modic changes (MCs) have been proposed as a distinct LBP phenotype, and inflammatory mediators may be involved in the development of MCs. Objectives: To identify possible serum biomarkers for LBP in patients with MCs. Methods: In this case control study serum levels of 40 cytokines were compared between patients with LBP and MC type 1 (n=46) or type 2 (n=37) and healthy controls (n=50). Results: Analyses identified significantly higher levels of six out of 40 cytokines in the MC type 1 group (MC1), and five in the MC type 2 group (MC2) compared with healthy controls. Six cytokines were moderately correlated with pain. Principal component analyses revealed clustering and separation of patients with LBP and controls, capturing 40.8% of the total variance, with 10 cytokines contributing to the separation. Macrophage migration inhibitory factor (MIF) alone accounted for 92% of the total contribution. Further, receiver operating characteristics analysis revealed that MIF showed an acceptable ability to distinguish between patients and controls (area under the curve=0.79). Conclusions: These results suggest that cytokines may play a role in LBP with MCs. The clinical significance of the findings is unknown. MIF strongly contributed to clustering of patients with LBP with MCs and controls, and might be a biomarker for MCs. Ultimately, these results may guide future research on novel treatments for this patient group.